Implications of evolving civil aviation safety regulations on the safety outcomes of air transport industry and airports - Yadav, D.; Nikraz, Hamid (2014)
Historically, the aviation industry has been highly regulated under national and international regulations and various agreements due to instinctive safety risks associated with operations of an aircraft. Therefore, safety sensitive aviation activities used to be regulated under prescriptive standards and regulatory regimes by respective national civil aviation authorities. Airports and commercial aircraft operators are experiencing tremendous commercial pressure due to the globalization and liberalization of the industry in recent years. Consequently, the civil aviation industry is moving progressively from prescriptive safety rules to performance based legislation. This paper analyses the significance of this regulatory shift in aviation safety. Furthermore, the potential safety risks associated with the outcome based legislative framework and deregulation of safety sensitive aviation activities are also indicated in this study together with an example of the maritime industry. © 2014 Copyright © 2014 Vilnius Gediminas Technical University (VGTU) Press.